Slip Partitioning in the 2016 Alboran Sea Earthquake Sequence (Western Mediterranean) - Stich, Daniel; Martín, Rosa; Morales, Jose; López-Comino, José Ángel; Mancilla, Flor de Lis (Frontiers in Earth Science, 2020)
A MW = 5.1 earthquake on January 21st, 2016 marked the beginning of a significant seismic sequence in the southern Alboran Sea, culminating in a MW = 6.3 earthquake on January 25th, and continuing with further moderate magnitude earthquakes until March. We use data from 35 seismic broadband stations in Spain, Morocco and Portugal to relocate the seismicity, estimate seismic moment tensors, and isolate regional apparent source time functions for the main earthquake. Relocation and regional moment tensor inversion consistently yield very shallow depths for the majority of events. We obtain 50 moment tensors for the sequence, showing a mixture of strike-slip faulting for the foreshock and the main event and reverse faulting for the major aftershocks. The leading role of reverse focal mechanisms among the aftershocks may be explained by the geometry of the fault network. The mainshock nucleates at a bend along the left-lateral Al-Idrisi fault, introducing local transpression within the transtensional Alboran Basin. The shallow depths of the 2016 Alboran Sea earthquakes may favor slip-partitioning on the involved faults. Apparent source durations for the main event suggest a ∼21 km long, asymmetric rupture that propagates primarily toward NE into the restraining fault segment, with fast rupture speed of ∼3.0 km/s. Consistently, the inversion for laterally variable fault displacement situates the main slip in the restraining segment. The partitioning into strike-slip rupture and dip-slip aftershocks confirms a non-optimal orientation of this segment, and suggests that the 2016 event settled a slip deficit from previous ruptures that could not propagate into the stronger restraining segment.